Utilization webGIS to map the distribution of health facilities in Tanjung Senang subdistrict Bandar Lampung City - Ningtyas, Ardilla Ayu; Miswar, Dedy; Utami, Rahma Kurnia Sri; Pargito, Pargito; Yarmaidi, Yarmaidi (Journal of Environment and Geography Education, 2024)
Background: Obstacles and problems in a developing health a facilities in the city of Bandar Lampung still occur in the Tanjung Senang subdistrict. Currently, there is no mapping of the distribution of health facilities in the area that is made spatially, attractively, and can be easily accessed by the wider community. Methods: This research aims to solve this problem by mapping the distribution of health facilities based on WebGIS, where all information on each health facility will be displayed spatially using QGIS, QGIS2Web plugin, leaflet, and webhosting. This research method is quantitative descriptive. Findings: The resulting product is WebGIS for the distribution of health facilities in Tanjung Senang District. The WebGIS that has been created is then validated by GIS experts, grammar experts, pragmatic experts, and users. Conclusion: The result of this research is the creation of a WebGIS which contains information on the distribution of health facilities (geographical conditions, accessibility, infrastructure, health workers, non-health workers, health services, and other supporting facilities). The score from the usability test was 86.05%. So that the WebGIS that has been created is very feasible, effective, and provides sufficient satisfaction for its users.